1998
DOI: 10.1172/jci2566
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 3 inhibitors suppress oocyte maturation and consequent pregnancy without affecting ovulation and cyclicity in rodents.

Abstract: During each reproductive cycle, a preovulatory surge of gonadotropins induces meiotic maturation of the oocyte in the preovulatory follicle followed by ovulation. Although gonadotropins stimulate cAMP production in somatic cells of the follicle, a decrease in intra-oocyte cAMP levels is required for resumption of meiosis in oocytes. Based on the observed compartmentalization of the cAMP-degrading enzyme, phosphodiesterase, in follicular somatic and germ cells, inhibitors of phosphodiesterase 3 were used to blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 33 publications
3
64
0
1
Order By: Relevance
“…Several years later, activity of the oocyte PDE3 was shown to increase before both spontaneous and gonadotrophin-induced meiotic resumption (Richard et al 2001). The effect of specific PDE3 inhibitors on maintaining oocyte meiotic arrest in vitro has now been demonstrated across many mammalian species: rats (Tsafriri et al 1996), mice (Wiersma et al 1998), cattle (Mayes & Sirard 2002, Thomas et al 2002, monkeys (Jensen et al 2002), humans (Nogueira et al 2003a) and swine (Laforest et al 2005). Demonstration of sterility of female mice bearing a PDE3A-null mutation due to the ovulation of GV-stage oocytes was the final proof of the central role of PDE3A in maintaining oocyte meiotic arrest (Masciarelli et al 2004).…”
Section: Cgmp and Phosphodiesterasesmentioning
confidence: 99%
“…Several years later, activity of the oocyte PDE3 was shown to increase before both spontaneous and gonadotrophin-induced meiotic resumption (Richard et al 2001). The effect of specific PDE3 inhibitors on maintaining oocyte meiotic arrest in vitro has now been demonstrated across many mammalian species: rats (Tsafriri et al 1996), mice (Wiersma et al 1998), cattle (Mayes & Sirard 2002, Thomas et al 2002, monkeys (Jensen et al 2002), humans (Nogueira et al 2003a) and swine (Laforest et al 2005). Demonstration of sterility of female mice bearing a PDE3A-null mutation due to the ovulation of GV-stage oocytes was the final proof of the central role of PDE3A in maintaining oocyte meiotic arrest (Masciarelli et al 2004).…”
Section: Cgmp and Phosphodiesterasesmentioning
confidence: 99%
“…Soluble forms of PDE3A exist in oocytes (Shitsukawa et al 2001), but the mechanisms of activation of the PDE3A remain unknown. Studies aiming to develop a new contraceptive strategy have shown that inhibition of PDE3A blocks oocyte meiosis in several species in vivo and in vitro (Tsafriri et al 1996, Wiersma et al 1998, Jensen et al 2002, Mayes & Sirard 2002, Nogueira et al 2003a.…”
Section: Introductionmentioning
confidence: 99%
“…The PDE3A activity in the regulation of oocyte maturation of several species has been studied extensively e.g. in rodent (Wiersma et al 1998), rat (Richard et al 2001), mouse (Masciarelli et al 2004;Nogueira et al 2003b;Nogueira et al 2005), monkey , porcine (Sasseville et al 2006;Sasseville et al 2007), bovine (Mayes and Sirard 2002;Thomas et al 2002), and human (Nogueira et al 2003a). Various PDE3 inhibitors were used like org9935, cilostamide, or milrinone.…”
Section: Phosphodiesterase 3a (Pde3a)mentioning
confidence: 99%